A Study of Biological Properties of Thiosemicarbazone Ligands and Their Transition Metal Complexes - poladian, qumars; Nabi, Tahera (Journal of Natural Sciences – Kabul University, 2023)
In this article, the biological properties of thiosemicarbazone ligands and their respective transition metal complexes are discussed. The biological activities of the aforementioned compounds are related to their unique structural properties, the nature of ligands and transition metals, and the presence of different substituents in the respective compounds of aldehyde, ketone, and thiosemicarbazide. The biological properties of thiosemicarbazones compared to standard drugs are generally evaluated using different methods such as real-time cell electronic sensing (RT-CES), MTT, and CUPRAC, and the results are included in tables and graphs. In this article, a review method with a descriptive-analytical approach is used, the results of which show more activity of the complexes compared to the primary ligands.